The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1103/physrevb.72.035215
|View full text |Cite
|
Sign up to set email alerts
|

Anion vacancies as a source of persistent photoconductivity in II-VI and chalcopyrite semiconductors

Abstract: Using first-principles electronic structure calculations we identify the anion vacancies in II-VI and chalcopyrite Cu-III-VI 2 semiconductors as a class of intrinsic defects that can exhibit metastable behavior. Specifically, we predict persistent electron photoconductivity (n-type PPC) caused by the oxygen vacancy V O in n-ZnO, and persistent hole photoconductivity (p-type PPC) caused by the Se vacancy V Se in p-CuInSe 2 and p-CuGaSe 2 . We find that V Se in the chalcopyrite materials is amphoteric having two… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
401
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 598 publications
(422 citation statements)
references
References 75 publications
18
401
3
Order By: Relevance
“…If the ionization energies of these defects are low, the system will tend to be an intrinsic n-type conductor. Some early studies have indicated that vacancies are shallow donors in these oxides [29][30][31][32][33][34][35][36][37][38], but more recent analysis based on plane-wave density functional theory (DFT), first using a Hubbard U parameter then, in later studies, a hybrid functional, tends to place them as deep centers in many TCOs [20,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Of those that have been shown to form shallow centers [41,[56][57][58][59], it has been argued that their compact wave functions preclude the possibility of them contributing to n-type conductivity [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…If the ionization energies of these defects are low, the system will tend to be an intrinsic n-type conductor. Some early studies have indicated that vacancies are shallow donors in these oxides [29][30][31][32][33][34][35][36][37][38], but more recent analysis based on plane-wave density functional theory (DFT), first using a Hubbard U parameter then, in later studies, a hybrid functional, tends to place them as deep centers in many TCOs [20,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Of those that have been shown to form shallow centers [41,[56][57][58][59], it has been argued that their compact wave functions preclude the possibility of them contributing to n-type conductivity [59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work mainly used local density approximation (LDA) or LDA+U (Ref. 2) Hamiltonians. These methods underestimate the band gaps of wide gap oxides 2 and so corrections to the band gap are necessary when calculating TL.…”
Section: Introductionmentioning
confidence: 99%
“…2) Hamiltonians. These methods underestimate the band gaps of wide gap oxides 2 and so corrections to the band gap are necessary when calculating TL. Here, we use the B3LYP hybrid density functional 9, 10 which predicts a single particle band gap for ZnO (3.17 eV, this work) in good agreement with experiment (3.47 eV (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…2 A second mechanism involves photoexcitation of an electron ͑or multiple electrons͒ from a deep donor into the conduction band, followed by a reconfiguration of the lattice that moves the ionized state of the deep donor well into the conduction band, say, to an energy E C + ⌬E. Lany and Zunger 18 have proposed such a mechanism for the oxygen vacancy V O , which in thermal equilibrium is deep ͑roughly E C −2 eV͒ and neutral. Their theoretical calculations find that if the two valence electrons of V O are excited ͑in separate steps͒ to the conduction band ͑while the trap-filling light is on͒ the resultant state V O ++ +2e − is pushed by the lattice reconfiguration into the conduction band to about E C + 0.2 eV.…”
Section: ͒mentioning
confidence: 99%